Corps et esprit : l’identité humaine selon Spinoza - Lamine Hamlaoui (Astérion)
Contrary to Descartes, Spinoza refuses to human mind and therefore to man the status of substance : man is defined as the union of two modes, body and mind. We can’t distinguish, as in Descartes, a substantial identity, conferred to the body by the mind, and a modal identity, determined by the relation between human body and other bodies. Both identities form an essential identity. This paper explains the problematical character of this identity in Spinoza’s Ethic. Human mind is indeed deduced and defined as the idea of human body, namely the concept of human body formed by God. But sometimes Spinoza identifies the idea of human body with the essence of human body, sometimes he makes a distinction between both. In the same way, sometimes he identifies the idea of human body with the idea of human mind, in accordance with parallelism of attributes, sometimes he distinguishes both. We can see, therefore, internal tensions in the system.